2019
DOI: 10.3892/ol.2019.9903
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin induces apoptosis of oral squamous cell carcinoma cells via G1 phase arrest and MAPK/Erk1/2 and Akt signaling inhibition

Abstract: Pristimerin is an active compound isolated from the traditional Chinese herbs Celastraceae and Hippocrateaceae. It has been reported to exert antitumor effects under experimental and clinical conditions; however, the antitumor effects and underlying mechanisms of pristimerin in oral cancer cells have not yet been identified. In the present study, the anticancer potential of pristimerin was investigated in two oral squamous cell carcinoma (OSCC) cell lines, CAL-27 and SCC-25. Results demonstrated that pristimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Multiple studies have revealed that some anti-cancer agents exert their effect by activating apoptosis, which is the major pharmacological mechanism in cancer therapy, including OSCC [ 36 , 37 , 38 ]. During apoptosis, the mitochondria and the activation of death receptors lead to the activation of caspase cascades [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have revealed that some anti-cancer agents exert their effect by activating apoptosis, which is the major pharmacological mechanism in cancer therapy, including OSCC [ 36 , 37 , 38 ]. During apoptosis, the mitochondria and the activation of death receptors lead to the activation of caspase cascades [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed that some anti-cancer agents exert their effect by activating apoptosis, which is the major pharmacological mechanism in cancer therapy, including OSCC [ 36 , 37 , 38 ]. During apoptosis, the mitochondria and the activation of death receptors lead to the activation of caspase cascades [ 38 , 39 ]. Previous studies have reported that IQ induces apoptosis via death receptor-mediated extrinsic pathway activation and the downregulation of anti-apoptotic proteins such as Bcl-2 and Bcl-xL, which are related to mitochondria-mediated apoptosis in colon cancer cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pristimerin exerts its effects influencing a series of biological properties of cancer cells. Recent studies on a wide range of cancer cell lines of different origins, such as oral cancer (Wu et al, 2019), colorectal cancer (Yousef et al, 2018), glioma (Yan et al, 2013), leukemia (Lu et al, 2010), breast cancer (Xie et al, 2016), lung cancer (Zhang et al, 2019), and prostate cancer (Liu et al, 2013), and also in cancer stem cells (Cevatemre et al, 2018). These results have proved that pristimerin possesses strong anti-proliferative activities with involvement of mitochondrial apoptosis, autophagy, and inhibition of nuclear factor kappa B (NF-κB), Akt (protein kinase B, PKB) and mitogen-activated protein kinase (MAPK) (Guo et al, 2013; Liu et al, 2013; Yan et al, 2013; Gao et al, 2014; Deeb et al, 2015).…”
Section: Pristimerin: Broad-spectrum Anti-cancer Effectmentioning
confidence: 99%
“…Pristimerin was first isolated in 1951 from Pristimerae indica and P. grahami and was first identified in 1954 to confirm its molecular structure (Kulkarni and Shah, 1954). Pristimerin has displayed different pharmacological effects, such as anti-cancer, anti-oxidant, anti-inflammatory, anti-bacterial, anti-malarial, and insecticidal activities (Figueiredo and Sequin, 1998; Avilla et al, 2000; Haroldo Jeller et al, 2004; Lopez et al, 2011; Kim et al, 2013; Wu et al, 2019). As such, it is being developed as a potential anti-cancer drug (Yousef et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, pristimerin showed more potent antiproliferative activity than chemotherapy drugs cisplatin and 5-fluorouracil. This effect was associated with inhibition of MAPK1/2 and PKB signaling pathways [367]. Pristimerin-induced apoptosis activity was also demonstrated in ovarian cancer cells via inhibition of AKT/NF-κB/mTOR signaling pathway [368].…”
Section: Pristimerinmentioning
confidence: 99%